Social Philanthropy Institutions in Indonesia: Review of Strategic Management Studies of Public Organizations in Social Philanthropy Institutions - Sastrawan, Panji; Hermawan, Dedy; Meliyana, Meliyana (Iapa Proceedings Conference, 2023)
This study aims to analyze the strategic management system implemented by social philanthropic institutions in Indonesia. The type of research used in this study is a literature study, library research (library research), and SWOT analysis. The results of the study show that there are three discussions: the philanthropic paradigm, funding or finance, and building an image or branding. The results of the SWOT analysis show that social philanthropic institutions in Indonesia are in quadrant 4, or ST. This quadrant describes the condition of philanthropic institutions that must reduce threats and take advantage of the strengths they have. The recommended strategy is a diversification strategy, in which social philanthropic institutions must develop strategies that can expand community outreach through various programs. Overall, philanthropic institutions in Indonesia, based on Hunger's theory (2009), are still in the early stages of basic financial planning, namely organizational and company planning based on financial planning.